Geochemical and hydrological aspects of interactions between water and mine waste - Shcherbakova, Elena (Luleå tekniska universitet, Geovetenskap och miljöteknik, 2006)
This thesis presents laboratory studies of sulphidic mine tailings remediated by flooding, and a pilot-scale study of dry cover for remediation of unoxidised sulphide-rich tailings. At the Kristineberg Zn-Cu mine in northern Sweden, sulphide-rich, poorly buffered tailings have been deposited in five impoundments located along a valley. By increasing pH by liming, thereby reducing metal mobility, a water-covered downstream impoundment is made to function as a trap for metals released from the till-covered impoundments upstream. As a result of the liming, a calcite-gypsum sludge has been formed on the tailings. The potential metal release from the sludge during resuspension events and in a long-term perspective was investigated by performing a shake flask test and sequential extraction of the sludge. A laboratory mixing experiment was performed to simulate the flocculation processes that occur in limed tailings ponds if stream water is diverted through a pond as a part of a remediation programme. The laboratory studies showed that the sequentially extracted carbonate and oxide fractions together contained ≥ 97% of the total amount of Cd, Co, Cu, Ni, Pb and Zn in the sludge. The association of these metals with carbonates and oxides appears to result from sorption and/or co-precipitation reactions at the surfaces of calcite and Fe, Al and Mn oxyhydroxides forming in the impoundment. In the shake flask test, remobilisation of Zn, Cu, Cd and Co (at a pH of 7-9) from the sludge resulted in dissolved concentrations of these metals that were significantly lower than those predicted to result from dissolution of the carbonate fraction of the sludge. This may suggest that cationic Zn, Cu, Cd and Co remobilised from dissolving calcite, gypsum and Al oxyhydroxides were readsorbed onto Fe oxyhydroxides remaining stable under oxic conditions. The laboratory mixing experiment showed that the flocculants that settled were rich in C (18 wt%) and acid leachable Fe (14-19wt%). Thus, organic matter and Fe oxyhydroxides appear to ...